EFFICIENCY OF NPK FERTILIZATION AND ADDITION OF BIODIVE FERTILIZERS ON THA PRODUCTION OF SOYBEAN (Glycine max (L) Merill) - Fenty Maimunah Simbolon; Muhammad Rizwan; Noverina Chaniago; Surya Agus Efendy (International Journal of Educational Research Excellence (IJERE), 2022)
This research was carried out at the Experimental Garden of the Faculty of Agriculture, Islamic University of North Sumatra, Jln. Eka Warni, Medan Johor District, Medan Municipality with a height of ± 25 meters above sea level with flat topography. The aim of the research was to determine the effect of providing biological fertilizer by reducing the dose of NPK fertilizer on soybean crop production. This research used the Factorial Randomized Block Design (RBD) method with two factors studied, namely: The first factor is bio quality (H) biological fertilizer which consists of 2 treatment levels, namely H 0 (Control), H 1 (10 cc/l water); The second factor is NPK fertilizer with 4 treatment levels, namely N 0 (Control), N 1 (20 g/plot), N 2 (40 g/plot) and N 3 (60 g/plot). The parameters observed were the number of pods per plant, seed weight per plant, production per plot and weight of 100 seeds. The results of the research showed that the application of bio quality biological fertilizer had a significant effect on production per plot and the number of pods per plant, but had no significant effect on the weight of seeds per plant and the weight of 100 seeds. Providing NPK fertilizer had a significant effect on the number of pods per plant and seed weight per plant , but had no significant effect on production per plot and the weight of 100 seeds. Meanwhile, the interaction between biological fertilizer and NPK fertilizer had a significant effect on production per plot and seed weight per plant, but had no significant effect on the number of pods per plant and the weight of 100 seeds.